2007
DOI: 10.1021/cm070708d
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Thermodynamic Studies of Silica Nanoparticle Dissolution

Abstract: Small-angle X-ray scattering (SAXS) and microcalorimetry were used to study the dissolution of silica nanoparticles that serve as precursors in the synthesis of the pure-silica zeolite, silicalite-1. Temporal changes in nanoparticle size were monitored by SAXS to obtain radial dissolution rates on the order of 1 × 10 -2 nm/min, 10 times greater than those of silicalite-1. Nanoparticle dissolution rates are independent of solution alkalinity (above pH 11) and particle surface area, although contributions from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
142
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(160 citation statements)
references
References 52 publications
(111 reference statements)
13
142
0
Order By: Relevance
“…Both hydrated and dehydrated ACC are high-energy metastable phases and there is a big energetic driving force for their crystallization. This large energy difference between hydrated amorphous and dehydrated crystalline phases is similar to the energetics of amorphous oxides such as zirconia and silica (39,40). The surface energies of the amorphous oxide materials are significantly smaller than those of their crystalline counterparts, suggesting that small particle size could lead to thermodynamic stabilization of amorphous relative to crystalline nanoscale materials (41,42).…”
Section: Discussionmentioning
confidence: 68%
“…Both hydrated and dehydrated ACC are high-energy metastable phases and there is a big energetic driving force for their crystallization. This large energy difference between hydrated amorphous and dehydrated crystalline phases is similar to the energetics of amorphous oxides such as zirconia and silica (39,40). The surface energies of the amorphous oxide materials are significantly smaller than those of their crystalline counterparts, suggesting that small particle size could lead to thermodynamic stabilization of amorphous relative to crystalline nanoscale materials (41,42).…”
Section: Discussionmentioning
confidence: 68%
“…The acid pH at which silica is exposed when removing polyamide 6 does not dissolve it. Perhaps there may be small changes on its structure, but it can be concluded that they are not significant at all, in agreement with the reported amorphous silica dissolution rates at different pH conditions [147].…”
Section: Changes In Materials Due To the Scaffold Fabrication Processsupporting
confidence: 85%
“…1.3 are reversed to produce again silanol groups. More current works [147] evaluate the dissolution of crystalline and vitreous silicas immersed at different pH conditions. The conclusion one can extract is the possibility to dissolve the acid catalyzed sol-gel silica which this work deals with.…”
Section: Changes In Materials Due To the Scaffold Fabrication Processmentioning
confidence: 99%
“…In situ microcalorimetry has been used to systematically study the thermochemical and thermokinetic properties of the synthesis process and crystal growth of rare-earth complexes [15][16][17]. This method has also been applied to the zeolite and silica system, and used to delineate the relationship between thermodynamic factors and changes in the solution chemistry and interface properties [18][19][20][21][22][23][24]. The formation mechanism of MCM-41 mesoporous silica was also investigated using microcalorimetry [25].…”
mentioning
confidence: 99%